Allergic Asthma: The Emerging Relationship Between the Gut Microbiome and Regulatory B Cells - Khan, Shawn; Niu, Candy (The Meducator, 2018)
As the global prevalence of allergic asthma continues to rise, there is growing interest in exploring the relationship between the gut microbiome of the host and the ability to regulate allergic inflammation. This was prompted by several studies that commonly demonstrated a correlation between the presence of microbial-rich environments and lower levels of childhood allergic asthma. With constant antigen exposure, the mucosal immune system of the gut must regulate environmental stimuli, such as bacteria and food antigens, to sustain immune homeostasis. This is achieved by maintaining immune tolerance to support the gut mucosa’s commensal microbiota and mounting a simultaneous, controlled immune response to eliminate pathogenic species. The immune patterns of the gut microbiome are thought to shape allergic asthma progression through its shared immunomodulatory role with the airway microbiome. Currently, studies are examining the role regulatory B cells play in allergic asthma through immune regulation. This review will discuss the relationship between regulatory B cells and the gut microbiome in maintaining immune homeostasis within the allergic disease framework.